Kasus Ikhtilath di Kabupaten Pidie: Tinjauan Terhadap Strategi Penyelesaian - Hamdiyah (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
The research method used to understand the mechanism of resolving cases of ikhtilath in Pidie District is qualitative research with direct data collection in the field. The results of the research show that cases of ikhtilath are not directly handled by the local village or sub-district authorities, but are handed over to the competent authorities because the perpetrators of ikhtilath often come from outside the area. This is done to ensure that the cases are resolved in accordance with the law and to deter the perpetrators and other members of the community. The mechanism for resolving cases of ikhtilath in Pidie District involves a legal process according to Qanun No. 6 of 2014. This process involves several parties, such as investigators, prosecutors, judges, and witnesses at the scene. Despite challenges such as limited resources and minimal budget, efforts are made to prevent ikhtilath through tighter security, family supervision, and community outreach. The sanctions imposed on perpetrators of ikhtilath are in accordance with existing regulations, but the lack of community participation in prevention and the shortage of PPNS investigators are inhibiting factors in handling these cases.